2020
DOI: 10.13106/jafeb.2020.vol7.no12.293
|View full text |Cite
|
Sign up to set email alerts
|

Ownership Structure, Earnings Manipulation, and Organizational Performance: The Case of Jordanian Insurance Organizations

Abstract: This study aims to investigate the direct relationship between ownership structure, earnings manipulation, and organizational performance, and then examine the mediating effect of earnings manipulation in the relationship between ownership structure and organizational performance. This study collected and analyzed secondary data published in financial reports related to all insurance organizations listed in the Jordanian market during the study period (from 2009 until 2018). A panel data analysis was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Agency theory was used in the majority of previous studies that looked at the relationship between audit quality and company financial performance and several of these studies have revealed that audit quality improves a company’s financial performance (Sayyar et al , 2015). According to Saidat et al (2019) and Alqirem et al (2020), the fundamental role of the control process in companies is to increase the efficiency and effectiveness of operational performance, to preserve the company’s reputation and to decrease agency conflicts between management and stakeholders. Jusoh et al (2013) and Farouk and Hassan (2014) documented that there is a negative relationship between audit quality and agency costs, because external auditors give an indicator of the legitimacy and integrity of financial reports, which may lead to an improvement in company performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Agency theory was used in the majority of previous studies that looked at the relationship between audit quality and company financial performance and several of these studies have revealed that audit quality improves a company’s financial performance (Sayyar et al , 2015). According to Saidat et al (2019) and Alqirem et al (2020), the fundamental role of the control process in companies is to increase the efficiency and effectiveness of operational performance, to preserve the company’s reputation and to decrease agency conflicts between management and stakeholders. Jusoh et al (2013) and Farouk and Hassan (2014) documented that there is a negative relationship between audit quality and agency costs, because external auditors give an indicator of the legitimacy and integrity of financial reports, which may lead to an improvement in company performance.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…This is performed through the use of accounting standards’ flexibility, or even by noncompliance, by modifying financial statements (Saleh et al , 2020a). Furthermore, there are studies that warn of risk behaviors and the elements that lead to these deviant attitudes on the part of managers and administrators, culminating in accounting fraud, with consequences not only for the companies but also for present and potential investors (Alqirem et al , 2020; Farouk and Hassan, 2014; Li, 2014; Phan et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our paper uses these proxies to measure the AQ. Accruals-based EMP using modified Jones model is regularly used in the previous studies (Alqirem et al, 2020;Chang and Sun, 2009). The modified Jones model is used to measure noncompulsory accruals to identify EMP (Dechow et al, 1995;Jones, 1991).…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…Francis et al (1999) suggested that high accrual firms are more probable to use a big auditor to have confirmation that income is reliable. Moreover, big firms tend to be more involved in EMP to accomplish a one-sided goal (Alqirem et al , 2020; Saleh et al , 2020a).…”
Section: Data Analysis and Findingsmentioning
confidence: 99%